2017
DOI: 10.1111/myc.12642
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary co‐infections by Pneumocystis jirovecii and Aspergillus fumigatus in non‐HIV patients: A report of two cases and literature review

Abstract: Pneumocystis jirovecii is the causative agent of Pneumocystis pneumonia (PcP), a common and often life-threatening opportunistic infection in HIV-infected patients. However, non-HIV, immunocompromised patients are at risk of PcP as well, whereas the mortality appears to be higher among these patients. Pneumocystis co-infections with other microorganisms are less frequent and only sparse reports of combined PcP and invasive pulmonary fungal infections exist in the literature, especially in the non-HIV patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…(4) PJP is an opportunistic infection. A part of PJP cases are associated with other fungi such as aspergillosis, which is considered a risk factor increasing the mortality of PJP (Markantonatou et al, 2017). Additionally, the level of BDG can also rise with some fungi such as aspergillosis and candida.…”
Section: Discussionmentioning
confidence: 99%
“…(4) PJP is an opportunistic infection. A part of PJP cases are associated with other fungi such as aspergillosis, which is considered a risk factor increasing the mortality of PJP (Markantonatou et al, 2017). Additionally, the level of BDG can also rise with some fungi such as aspergillosis and candida.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coinfection with multiple strains of P. jirovecii, there are considerable case reports of pulmonary coinfection of P. jirovecii with one or more other pathogens, including Aspergillus spp. (479)(480)(481)(482), Cryptococcus spp. (483)(484)(485), Candida spp.…”
Section: Strain Variation Of P Jiroveciimentioning
confidence: 99%
“…Despite increasing reports of P. jirovecii colonization, there are only a few studies of coinfection with other respiratory pathogens in patients with P. jirovecii colonization [40][41][42]. Our study found that the majority of individuals with P. jirovecii colonization had concurrent infections with other fungal or bacterial pathogens (Table 4).…”
Section: Discussionmentioning
confidence: 47%